Transformasi Hukum Penguasaan dan Pemanfaatan Sumber Daya Alam Berbasis Keadilan Progresif di Indonesia - Angela Davina Ryan Vie; Hauna Tsabitul Azmi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
The governance of natural resources (NR) in Indonesia remains marked by structural inequalities that favor large corporations, while indigenous and local communities are marginalized from access, management rights, and equitable benefit-sharing. Although the Constitution and several laws mandate social justice and ecological sustainability, NR governance practices tend to focus on exploitation and investment acceleration, sacrificing environmental protection and meaningful public participation. This study employs a normative juridical approach to analyze weaknesses in sectoral regulations, overlapping authorities, and their implications for the rights of local communities. Drawing on Satjipto Rahardjo’s progressive justice theory, it offers a reformulation of the concept of “controlled by the state” in Article 33 of the 1945 Constitution as a trustee mandate, rather than a monopoly, placing humans, the environment, and justice as the primary orientation. The proposed legal transformation strategies include revising NR regulations, implementing the Free, Prior, and Informed Consent (FPIC) principle, strengthening community-based management models, recognizing the rights of nature, and establishing participatory oversight mechanisms. This approach is expected to dismantle unequal power relations and direct NR governance toward ecological sustainability, community empowerment, and intergenerational benefit equity.